Encapsulation of pancreatic islet with HMGB1 fragment for attenuating inflammation. Issue 1 (December 2015) - Jo, Eun; Hwang, Yong; Lee, Dong
Abstract Background Pancreatic islet encapsulation is one way to address the disadvantages of islet transplantation. Not only does encapsulation involve bidirectional diffusion of nutrients, oxygen, and glucose, but also it protects the graft from the recipient's immune reaction. The high mobility group box 1 (HMGB1), one of higher expression proteins in islet, can be secreted from transplanted islets and induce the inflammation. Therefore, the regulation of HMGB1-mediated inflammation is very important for successful islet transplantation. In this study, we used the HMGB1 A box, an antagonist of HMGB1 receptor in the immune cells, in the encapsulation of isolated islets as a new strategy. Result For co-encapsulation of HMGB1 A box protein with islets, we evaluated the distribution of alginate bead diameter. The average diameter of empty alginate bead was similar to that of alginate bead with islets. When different concentrations of HMGB1 A box protein was co-encapsulated with islets, it did not affect the viability and insulin secretion function of the islets. When the alginate beads with islets plus HMGB1 A box protein were cultured with macrophage, the amount of TNF-α secreted from the macrophages was significantly attenuated when compared to cultivation of unencapsulated islets or encapsulated islets. When the alginate beads with islets plus HMGB1 A box protein were intraperitoneally xenotransplanted into the diabetic mice, the survival rate of the islets was strongly improved with 2-fold. Conclusion Collectively, these results suggested that the encapsulation of HMGB1 A box protein might offer a protective effect in islet transplantation.